2017
DOI: 10.1186/s12955-017-0657-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of depressed and suicidal patients seeking services from traditional and faith healers in rural Kenya

Abstract: BackgroundIn rural Kenya, traditional and faith healers provide an alternative pathway to health care, including mental health care. However, not much is known about the characteristics of the populations they serve. The purpose of this study was to determine the relationship between depression, suicidal ideation, and socio-demographic variables with Quality of Life (QoL) indicators in a sample seeking mental health services from traditional and faith healers in rural Kenya. Understanding QoL in this sample ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The average BSSI score (4.72 vs. 13.1) also decreased between pre-protocol and post-protocol evaluation. The BSSI scores were high (reference scores [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] before the intervention and dropped to average after treatment (reference scores of [4][5][6][7][8][9][10]. No safety issues were observed with the BCC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The average BSSI score (4.72 vs. 13.1) also decreased between pre-protocol and post-protocol evaluation. The BSSI scores were high (reference scores [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] before the intervention and dropped to average after treatment (reference scores of [4][5][6][7][8][9][10]. No safety issues were observed with the BCC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A psychological autopsy study found that low QoL within the month before death was a significant predictor of completed suicide ( 17 ). Musyimi et al ( 18 ) reported that based on their cross-sectional epidemiological survey conducted over a period of 3 months among adult patients seeking care from traditional and faith healers in rural Kenya, regression analysis indicated that depression, suicidal ideation, and being married predicted lower overall QoL controlling for other variables.…”
Section: Introductionmentioning
confidence: 99%
“…One study in Nigeria showed that providing traditional healers with basic training led to traditional healers recognising more symptoms of major mental illnesses, better understanding the aetiological concepts of mental illness, reducing the habit of beating their patients as a form of treatment, and increasing their collaborative outlook. 22 More recent collaborative work with traditional healers in Kenya for patients with depression, [23][24][25] and mental health-related task expansion with traditional birth attendants, 26 have shown very positive and inspiring results, and have highlighted this important topic. 27,28 The current study reports on a now well-established collaboration in Addis Ababa, Ethiopia, and focuses on the process for initiating a successful collaboration.…”
mentioning
confidence: 99%